Contextualization of Educational Management in the School, Family and Social Environments: Literature Study on the Concept of Islamic Education - Adinda Laili Nur Farida; Fauzan Alim; Hamdu Maulana; Vino Sukmana Huda; Latif Syaipudin (Beginner: Journal of Teaching and Education Management, 2023)
This research discusses the contextualization of educational management in the community environment, which is divided into school, family and social environments. These three environments are one of the fundamental aspects of the educational management process that must be implemented. The formulation of the problem in this research is what is the concept of educational management in the scope of Islamic education? This research method uses a literature study approach, with data collection techniques using relevant research studies and several expert theories and verses from the Koran related to educational management. The results of this research show that there are three points, first, educational management in the school context, namely the concept of management in the school context is very important, because it can be an effort to achieve the goals of quality education. Planning in school management involves setting educational goals, developing curriculum, and planning learning activities. Second, discussing family education management, this is a management concept that is in line with family education which is the key to creating a home environment that supports positive growth and development of children. Third, namely educational management in the social sphere of society is an important foundation in ensuring quality and inclusive education for all individuals in society.